Effects of wolfberry (Lycium barbarum) consumption on the human plasma lipidome and its association with cardiovascular disease risk factors: a randomized controlled trial of middle-aged and older adults - Toh, Darel Wee Kiat; Zhou, Hanzhang; Cazenave-Gassiot, Amaury; Choi, Hyungwon; Burla, Bo; Bendt, Anne Katherin; Wenk, Markus R.; Ling, Lieng Hsi; Kim, Jung Eun (Frontiers in Nutrition, 2024)
Background: Long-term wolfberry intake as part of a healthy dietary pattern was recognised to have beneficial vascular outcomes. Characterization of the plasma lipidome may further provide comprehensive insights into pathways underlying these cardiovascular protective effects. Objective: We analyzed the plasma lipidome of subjects who adhered to a healthy dietary pattern either with or without wolfberry and investigated the associations between the plasma lipidomic profile and cardiovascular health-related indicators. Methods: In this 16-week, parallel design, randomized controlled trial, middle-aged and older adults (n = 41) were provided dietary counseling and assigned to either consume or not consume 15 g of wolfberry daily. At baseline and post-intervention, plasma lipidomics was assayed, and its relationships with classical CVD risk factors, vascular health, oxidant burden, carotenoids status, body composition and anthropometry were examined. Results: From the plasma lipidome, 427 lipid species from 26 sub-classes were quantified. In the wolfberry and control groups, significant changes were prominent for 27 and 42 lipid species respectively (P < 0.05 with > 0.2-fold change). Fold changes for 7 lipid species were also markedly different between the two groups. Examining the relationships between the plasma lipidome and CVD-related risk factors, total cholesterol revealed a marked positive correlation with 13 ceramide species, while HDL-cholesterol which was notably increased with wolfberry consumption showed a positive correlation with 10 phosphatidylcholine species. Oxidant burden, as represented by plasma 8-isoprostanes, was also inversely associated with lipidomic triglycerides and ether-triglycerides (41 species) and directly associated with hexosylceramides (8 species) and sphingomyelins (6 species). There were no differential associations with CVD risk detected between groups. Conclusion: Characteristic alterations to the plasma lipidome were observed with healthy dietary pattern adherence and wolfberry consumption. An examination of these fluctuations suggests potential biochemical mechanisms that may mediate the antioxidant and cardiovascular protective effects of healthy dietary pattern adherence and wolfberry intake. This study was registered at clinicatrials.gov as NCT0353584